Pareceristas ad hoc 2012 - admin, Administrador (Outros Tempos: Pesquisa em Foco - História, 2013)
Ana Livia Bomfim Vieira - Universidade Estadual do Maranhão Alírio Cardoso - Universidade Federal do Maranhão Antonio Otaviano Vieira Junior - Universidade Federal do Pará Claudia Cristina Azeredo Atallah - Universidade Severino Sombra Cláudio Zannoni - Universidade Federal do Maranhão Edson Silva - Universidade Federal de Pernambuco Esteban Ticona Alejo - Universidad Mayor De San Andres-La Paz Eudes Leite – Universidade Federal da Grande Dourados Fernanda Fioravante Kelmer Mathias - Universidade Federal Rural do Rio de Janeiro Francisco Javier Laviña Gomez – Universidade de Barcelona George Félix Cabral – Universidade Federal de Pernambuco José Sampaio de Matos Júnior - Universidade Estadual do Maranhão Marcelo Cheche Galves - Universidade Estadual do Maranhão Maria Da Glória Porto Kok - Universidade de São Paulo José Alves de Souza Junior - Universidade Federal do Pará Josenildo de Jesus Pereira - Universidade Estadual do Maranhão José Ruiz peinado – Universidade de Baracelona Jorge Victor de Araújo Souza – Universidade Severino Sombra Karl Heinz Arenz - Universidade Federal do Pará Kátia Rodrigues Paranhos - Universidade Federal de Uberlândia Márcia Milena Galdez - Universidade Estadual do Maranhão Mairton Celestino - Universidade Federal do Piauí Miliandre Garcia - Universidade Estadual de Londrina Paulo Roberto Cimó Queiroz - Universidade Federal da Grande Dourados Pollyanna Gouveia Mendonça Muniz - Universidade Federal do Maranhão Rafael Ivan Chambouleyron – Universidade Federal do Pará Bentes Monteiro - Universidade Federal Fluminense Rômulo Luiz Xavier do Nascimento - Universidade Federal de Pernambuco Silvia Patuzzi – Pontifícia Universidade Católica-RJ/ Fundação Getúlio Vargas/RJ Tatiana Raquel Reis Silva - Universidade Estadual do Maranhão Wlamir José da Silva - Universidade Federal de São João del-Rei